Cover Feature: Total Syntheses of (+)‐Villocarine A, (−)‐Apogeissoschizine, and (+)‐Geissoschizine (Chem. Eur. J. 18/2023). Issue 18 (22nd February 2023) - Sakamoto, Jukiya; Kitajima, Mariko; Ishikawa, Hayato
Abstract : Geissoschizine is a very important biosynthetic intermediate of monoterpenoid alkaloids in higher plants. In this study, the enantioselective and stereodivergent total syntheses of geissoschizine and two related indole alkaloids (villocarine A and apogeissoschizine) were achieved. The three synthesized natural products are represented as Nishikigoi (varicolored carp), which are also called "swimming jewels" in Japan, and the cascade reaction is represented by their graceful swimming along a river. More information can be found in the Research Article by H. Ishikawa and co‐workers (DOI: 10.1002/chem.202300179 ).